Prevalence and risk factors for dental caries among 3-year-old children in Shanghai, China: a cross-sectional study - Shuran Yao; Jing Zhu; Hao Zhang; Huning Wang; Dongxin Da; Jin Yu; Yiwei Jiang; Hongru Su; Hongyan Shi; Qiwen Chen; Zhengang Wu; Jiangtao You; et al. (BMC Oral Health)
Abstract Background Early childhood caries (ECC), especially severe early childhood caries (SECC), severely affects children’s oral health, causing pain and tooth loss. This study aimed to investigate the prevalence of dental caries among 3-year-old children in Shanghai, China, and to identify associated risk factors. Methods This cross-sectional study involved 1,241 3-year-old children from six Shanghai districts, selected via stratified random sampling. The study used an oral health questionnaire and clinical examinations by trained examiners following WHO guidelines. Dental caries were diagnosed using WHO criteria, with dmft scores indicating caries presence (≥ 1) and SECC defined as ≥ 4. Caregiver-completed questionnaires gathered data on oral hygiene practices and sociodemographic information. Statistical analyses included the Mann-Whitney U test, Kruskal-Wallis H test, chi-square test, logistic regression, and zero-inflated negative binomial (ZINB) regression. Results The prevalence of dental caries among 1241 children was 25.00%, with a mean dmft score of 0.98. The prevalence of SECC was 9.43%. The significant caries index (SiC) and SiC10 were 2.94 and 7.02, respectively. Logistic regression analysis indicated that consuming sugar-sweetened beverages (OR = 1.65, 95% CI 1.07–2.55, p < 0.05), eating after bedtime brushing (OR = 1.62, 95% CI 1.01–2.59, p < 0.05), the age at which tooth brushing commenced (OR = 2.63, 95% CI 1.40–4.96, p < 0.05), and the mother’s education level (OR = 1.61, 95% CI 1.07–2.43, p < 0.05) were associated with SECC occurrence. ZINB regression analysis revealed that consuming sugar-sweetened beverages (OR = 0.45, 95% CI 0.15–0.74, p < 0.05) and eating after bedtime brushing (OR = 0.67, 95% CI 0.34–1.01, p < 0.001) were associated with the incidence of dental caries, whereas the age at which tooth brushing commenced (IRR = 1.58, 95% CI 1.13–2.20, p < 0.05) and the mother’s education level (IRR = 1.47, 95% CI 1.15–1.87, p < 0.05) were related to the dmft score. Conclusions The prevalence of dental caries among 3-year-old children in Shanghai is low, yet the rate of SECC remains a concern. SECC is associated with factors including the frequency of sugar-sweetened beverage intake, post-toothbrushing eating habits, age of toothbrushing initiation, and mother’s education level.